Neurobehavioral effects of treatment for opiate withdrawal. Issue 1 (21st December 2004) - Coyle, M G; Ferguson, A; LaGasse, L; Liu, J; Lester, B
Abstract : A partially randomised, controlled trial was performed to test the hypothesis that opiate exposed infants treated with diluted tincture of opium (DTO) and phenobarbital would have better neurobehavioral scores than infants treated with DTO alone. Compared with those treated with DTO alone (n = 15), infants treated with DTO and phenobarbital (n = 17) were more interactive, had smoother movements, were easier to handle, and less stressed. Dual treatment results in improved neurobehavioral organisation during the first three weeks of life, which may indicate a more rapid recovery from opiate withdrawal.